2021
DOI: 10.1186/s12879-021-06664-w
|View full text |Cite
|
Sign up to set email alerts
|

Case report: change of dominant strain during dual SARS-CoV-2 infection

Abstract: Background The dual infection with SARS-CoV-2 is poorly described and is currently under discussion. We present a study of two strains of SARS-CoV-2 detected in the same patient during the same disease presentation. Case presentation A patient in their 90 s was hospitalised with fever. Oropharyngeal swab obtained on the next day (sample 1) tested positive for SARS-CoV-2. Five days later, the patient was transferred to the ICU (intensive care unit) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Recombination can occur when the same host is coinfected by two different strains, which has been noted to occur in COVID-19 patients ( Samoilov et al 2021 ), and could become more likely with the emergence of more transmissible variants. We note that the potential mosaic sequences we identified in the South Africa sample from November are represented only once in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Recombination can occur when the same host is coinfected by two different strains, which has been noted to occur in COVID-19 patients ( Samoilov et al 2021 ), and could become more likely with the emergence of more transmissible variants. We note that the potential mosaic sequences we identified in the South Africa sample from November are represented only once in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dual SARS-CoV-2 infection has been studied with two phylogenetically distant strains. The initially dominant strain belonged to GH clade and was suppressed by another strain from the GR clade, in only eight days ( Samoilov et al, 2021 ). The initial ratio of the GH to GR strain was 70:30, while 8 days later it became 3:97, obviously as a result of interference ( Samoilov et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The initially dominant strain belonged to GH clade and was suppressed by another strain from the GR clade, in only eight days ( Samoilov et al, 2021 ). The initial ratio of the GH to GR strain was 70:30, while 8 days later it became 3:97, obviously as a result of interference ( Samoilov et al, 2021 ). Thus, we have observed interference between various strains of SARS-CoV-2 ( Korber et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [ 48 ] reported a case where one patient was infected by 2 different SARS-CoV-2 strains simultaneously. According to the authors, two samples (Sample1 and Sample2) were obtained from the same patient 8 days apart and both samples were found to contain two highly similar SARS-CoV-2 strains from different clades.…”
Section: Resultsmentioning
confidence: 99%
“…All SARS-CoV-2 single-strain sequencing datasets used in this manuscript can be downloaded from the NCBI SRA database ( https://www.ncbi.nlm.nih.gov/sra ) [ 61 ] with accession numbers: SRR10971381, SRR11593364, SRR11880659, SRR13644068, SRR12546786, ERR4387386, SRR12528370, SRR11513776, SRR11570921, SRR13634208, SRR11593362, SRR11593358, SRR13574086, SRR13574250, SRR13574082, SRR13644095, SRR13718002, SRR13684392, SRR13644074, SRR13681138, SRR13684393, SRR13499395, SRR13499389, SRR13499360, SRR11968882, SRR12316191, SRR12588591, SRR12598969, SRR12598968, SRR12352751, SRR12352750, and SRR11587603. The SARS-CoV-2 mix-strain sequencing datasets are downloaded from [ 48 ] (SRA accession number: SRR14142136 and SRR14142137). The HIV 5-strain mock data is downloaded from [ 49 ] (SRA accession number: SRR961514).…”
mentioning
confidence: 99%